The Combination of Intravenous Immunoglobulin, Dexamethasone, and a High Dose of Mononuclear Cells Transfusion: An Effective Strategy for Decreasing Donor-Specific Antibodies During Haploidentical Hematopoietic Stem Cell Transplantation - Xiaoping Li; Yu Li; Dingsong Zhang; Xiaozhuang Hu; Lin Liu; Zhongtao Yuan; Shiqi Li; Yancheng Dong; Yingnian Chen; Sanbin Wang (Cell Transplantation)
Donor-specific antibodies (DSAs) are essential causes of graft rejection in haploidentical hematopoietic stem cell transplantation (haplo-HSCT). DSAs are unavoidable for some patients who have no alternative donor. Effective interventions to reduce DSAs are still needed, and the cost of the current therapies is relatively high. In this study, we retrospectively analyzed the data of 11 DSA-positive patients who received haplo-HSCT at our center and evaluated the therapeutic efficacy of the combination of intravenous immunoglobulin (IVIG), dexamethasone and high dose of transfused mononuclear cells (MNCs) for DSA desensitization. The kinetics of DSAs at different times and the engraftment and transplantation outcomes were also observed. We found that all patients had successful donor-cell engraftment and that no patient developed poor graft function. The median engraftment times of neutrophils and platelets were 14 days (range, 11–24 days) and 13 days (range, 11–123 days), respectively. The DSA levels of all patients became negative or dropped under 2000 within 22 days after HSCT. A total of 36.4% of patients developed grade II–IV acute graft-versus-host disease (aGVHD), and 9.1% of patients died of severe gastrointestinal aGVHD. Of the 7 surviving patients, four were diagnosed with chronic GVHD. After a median follow-up of 28.9 months (2.0–52.1 months), four patients died: of relapse (two), aGVHD (one), and multiple-organ failure (one). The 2-year OS, DFS, and NRM were 63.6%, 45.4%, and 18.2%, respectively. Combination therapy with IVIG, dexamethasone, and a high dose of MNCs transfusion, a simple and efficient procedure, was safe and effective for DSA desensitization and peripheral blood stem cell (PBSC) engraftment.